Estimating Non-Conductive Heat Flow Leading to Intra-Permafrost Talik Formation at the Ritigraben Rock Glacier (Western Swiss Alps) - Luethi, Rachel; Phillips, Marcia; Lehning, Michael (Permafrost and Periglacial Processes, 2016)
Although non-conductive heat flow plays an important role in the evolution of rock glacier temperature and dynamics, few studies have quantified it. At the Ritigraben rock glacier (Switzerland), intra-permafrost talik formation was observed at around 12m depth and related to snowmelt and rainfall infiltration. Our aim is to attribute the talik formation to physical processes by quantifying the heat required to explain the observed dynamics of the temperature profile. We combined measured borehole temperatures, meteorological data and borehole logs with physics-based modelling experiments using the one-dimensional SNOWPACK model. The simulations were run with a simulated heat sink/source controlled by modelled snow cover, measured meteorological data and borehole temperature measurements. This allowed us to estimate non-conductive heat flow for different synthetic ground profiles with varying physical properties based on borehole logs. Our model results corroborate the assumption that purely conductive heat exchange is incompatible with the observed talik formation. We attribute the talik to advective and conductive heating by infiltrating water (which causes local heating rates to the order of 1Wm(-3)) and circulating air (which causes cooling to the order of 0.1Wm(-3)). Copyright (c) 2016 John Wiley & Sons, Ltd. Copyright (c) 2016 John Wiley & Sons, Ltd.